2010
DOI: 10.1007/s10661-010-1478-4
|View full text |Cite
|
Sign up to set email alerts
|

A long-term survey of heavy metals and specific organic compounds in biofilms, sediments, and surface water in a heavily affected river in the Czech Republic

Abstract: To assess the long-term anthropogenic load of the Bílina River (Czech Republic), the concentrations of heavy metals and specific organic compounds in different river ecosystem matrices (water, biofilms, and sediments) were determined. Although the current concentrations of pollutants in surface water are low, frequently below the limits of the quantitative analytical methods used, the river ecosystem is still heavily loaded by anthropogenic pollution, mainly from the chemical and mining industries. This was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 49 publications
2
22
0
Order By: Relevance
“…Higher TEs contents are accompanied by higher contents of various POPs of industrial as well as agricultural origin (HCB, HCHs, DDT, and metabolites). Similar ecosystem contamination caused by anthropogenic sources was reported by Kohušová et al (2011) in the adjacent watershed of the Bílina River.…”
Section: Resultssupporting
confidence: 82%
“…Higher TEs contents are accompanied by higher contents of various POPs of industrial as well as agricultural origin (HCB, HCHs, DDT, and metabolites). Similar ecosystem contamination caused by anthropogenic sources was reported by Kohušová et al (2011) in the adjacent watershed of the Bílina River.…”
Section: Resultssupporting
confidence: 82%
“…The source of pollution is waste water from industry, municipal sewage, agricultural procedures, and mining activities (Kohusova et al 2011). The results of a long-term study by Kohusova et al (2011) indicated that the middle and the lower stretches of the Bílina River were heavily polluted by metals and organic pollutants. The main sources of pollution were oil, coal, the chemical industry, and municipal sewage.…”
Section: Discussionmentioning
confidence: 99%
“…A general observation is that the concentrations of these heavy metals did not have a seasonal variation feature and that the variation of the various heavy metals with time was very different. This indicates that the changes in these concentrations were mainly influenced by anthropogenic activities, rather than natural processes (Kohušová et al 2011;Li and Zhang 2010). The results show that the concentrations of As, Cr(VI), and Pb were much higher than those of Hg and Cd over this period.…”
Section: Resultsmentioning
confidence: 75%